PHYTOSOCIOLOGY OF WEEDS IN OFF-SEASON MAIZE CROPS IN THE MIDDLE PARANAPANEMA - Gazola, T. [UNESP]; Dias, M. F. [UNESP]; Duarte, A. P.; Carbonari, C. A. [UNESP]; Velini, E. D. [UNESP] (Univ Federal Vicosa, 2018)
This work is the first one after the consolidation of the introduction of the RR technology in maize and soybean crops, following weed surveys previously carried out in the region of the Middle Paranapanema, Sao Paulo state. The objective was to carry out a phytosociological survey of weeds in off-season maize crops notillage, in the same properties where the studies had been previously carried out, in the described region, taking into account the management of the weed community adopted by fanners, and the percentage of plant coveron the soil. The surveys were carried out in 19 farms conducted under no-tillage systems, with off-season maize cultivated in soybean succession, both RR crops, in nine municipalities of the Sao Paulo region of the Middle Paranapanema, in 2016. The main weeds were Bidens pilosa, Cenchrus Echinatus, Commelina benghalensis, Digitaria horizontalis, Gnaphalium spicatum, Leonotis nepetifolia, Raphanus sativus and Sonchus oleraceus. The predominant management of weeds was the chemical method, and in the vast majority of properties, control was based on the use of glyphosate and atrazine. The other used heibicides are nicosulfuron, chlorimuron-ethyl, clethodim, haloxyfop, tembotrione and 2,4-D, almost always associated with the EPSPs inhibitor. The soil cover with straw, found at the time of the evaluation, had no correlation with the presence or absence of the weeds.
Keywords: heibicides; weeds; no-tillage; Zea mays